The significance of MRD-based strategy by dynamic assessment to guide treatment decisions in B-ALL – the enlightenment provided by demonstrating survival differences in the retrospective study - Yongyu Chen; Rongrong Liu; Jing Li (Hematology)
Purpose: The study aimed to access the impact of related factors on the long-term survival of patients with B-cell acute lymphoblastic leukemia (B-ALL) by analyzing clinical characteristics of B-ALL patients, and observed the significance of dynamic measurable residual disease (MRD) assessment for the prognosis and treatment selection of B-ALL patients, aiming to deepen the understanding of the disease and improve the survival prognosis of B-ALL patients.Methods: The clinical characteristics of 65 patients with B-ALL were collected to calculate the median overall survival (OS) and median disease-free survival (PFS), and to evaluate the significance of survival analysis guided by dynamic MRD assessment.Results: The survival analysis based on dynamic MRD assessment suggested that B-ALL patients who maintained MRD negative status during dynamic assessment after induction chemotherapy had better survival outcomes in the comparison of progression-free survival between subgroups, with statistically significant differences (P = 0.0002 (HR: 0.26, 95% CI: 0.13-0.51)). High-risk B-ALL patients who maintained negative MRD status during dynamic assessment after induction chemotherapy had longer median progression – free survival, and the survival difference between subgroups was statistically significant (P = 0.0016 (HR: 0.28, 95% CI: 0.09-0.48)).Conclusion: Dynamic MRD assessment had significant clinical value: maintaining negative MRD status during dynamic assessment can improve the prognosis and survival of B-ALL patients; dynamic MRD assessment after induction chemotherapy can help guide subsequent treatment, which could provide reference for the advancement of future treatment strategies.